Newest approaches in ligament injury treatment: platelet-rich plasma (PRP) and stem cells - Kamijantono, Harry; Sebayang, Moriko Madadoni; Lesmana, Andrean (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Ligaments are strong connective tissues that connect bones to other bones, providing stability and supporting joint movement. Ligament injuries are a serious issue often experienced by athletes and active individuals, which can lead to pain, swelling, and reduced joint function. The treatment for ligament injuries varies depending on the severity of the injury and individual needs. Purpose: To determine the effectiveness of these two methods in accelerating the healing process and reducing the risk of complications. Method: A qualitative study using a literature review approach. Data collection was derived from various written sources, such as scientific journals, books, conference articles, and research reports. The data analysis technique involves several important steps: conducting extensive literature searches using relevant keywords, selecting literature based on its relevance and quality, thoroughly reading and understanding the content of the literature, recording important information, key findings, and interpretations presented by the authors. Once the data was gathered, the researcher performed synthesis and thematic analysis, organizing the findings into themes or categories aligned with the research topic. Results: Out of 70 articles initially retrieved from Scopus, 9 articles were selected after undergoing a screening process based on predetermined criteria. Conclusion: The use of PRP in the treatment of ligament injuries shows promising results in terms of accelerating recovery time and reducing patient pain. New therapies for ligament injury treatment using PRP and stem cells are highly promising in improving treatment outcomes and speeding up patient recovery.